Designing a Website-Based Study Program Management Application and Digital Attendance for Informatics Study Programs - Dwi Tri Putra, Bainul; Labiba Sarwoko, Nisrina; Gian Febriantama, Rizal; Bintang Maharani Sigalingging, Miranda; Naufal Arits Fikri, Muhammad; Ahmad Firdaus, Eryan (Marqcha Institute, 2025)
Conventional attendance and conventional management of academic activities often cause problems, such as recording errors, delays, and lack of access to organized information. In addition, academic communication still relies on external platforms, such as Telegram, which does not support the needs of lecture activity management. This research aims to design a web-based application called ClassTIcs, which provides digital attendance features, lecture schedule management, lecture material upload, and textbased discussion forums. This application involves three main actors: staff as super admin, lecturers, and students. The research uses the Rapid Application Development (RAD) method, which includes the stages of requirements planning, system design, prototype development, and testing. With ClassTIcs, staff can manage attendance data and schedules, lecturers can conduct digital attendance and upload lecture materials, and students can monitor lecture schedules and discuss through text forums. The results show that this application can help overcome the obstacles that often arise in the attendance process and management of study program activities while providing convenience for all actors involved. Further development is recommended to add other features to support the various needs of study programs in the future.